Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.15829/1560-4071-2016-2-30-36
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Three-Week Aerobic Exercise Program on Neurodynamic Parameters of Patients Underwent Coronary Bypass Grafting

Abstract: Цель. Оценить влияние трехнедельного курса аэробных физических трениро-вок на показатели когнитивного статуса пациентов, подвергшихся коронар-ному шунтированию (КШ). Материал и методы. Обследовано 92 мужчины с ишемической болезнью сердца (ИбС), перенесших КШ в условиях искусственного кровообращения (ИК). Пациенты были разделены на 2 группы: в первой группе -39 человек (средний возраст -55,5±5,3 лет) проводился трехнедельный курс велотре-нировок, во второй группе -53 человека (57,2±6,21 лет) велотренировки не п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…Physical rehabilitation has been shown to reduce muscle mass loss and the number of postoperative respiratory complications during the postoperative period of cardiac surgery (Borghi-Silva et al, 2005;Balady et al, 2011;Kamarajah et al, 2020). The study by Argunova et al (2016) showed that the use of PhT postoperatively reduces cognitive impairment in patients after CABG. However, the effectiveness of physical rehabilitation in the preoperative period of cardiac surgery is currently under active study (Argunova et al, 2017(Argunova et al, , 2018Waite et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical rehabilitation has been shown to reduce muscle mass loss and the number of postoperative respiratory complications during the postoperative period of cardiac surgery (Borghi-Silva et al, 2005;Balady et al, 2011;Kamarajah et al, 2020). The study by Argunova et al (2016) showed that the use of PhT postoperatively reduces cognitive impairment in patients after CABG. However, the effectiveness of physical rehabilitation in the preoperative period of cardiac surgery is currently under active study (Argunova et al, 2017(Argunova et al, , 2018Waite et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of aerobic PhT on cognitive function in patients undergoing cardiac surgery have rarely been studied. For example, a recent study found that a 3-week course of daily PhT after cardiac surgery contributed to the reduction of postoperative cognitive dysfunction (POCD) incidence in patients with coronary artery disease (Argunova et al, 2016). To date, no studies have examined the possible effects of aerobic physical prehabilitation on cognitive function in the postoperative period of cardiovascular surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Преимущество этого метода у пациентов с ИБС заключается в том, что, помимо протективных эффектов вследствие воз-действия ишемического прекондиционирования, физические тренировки обладают доказанной эффективностью в отношении снижения показа-телей общей и сердечно-сосудистой смертности, повышения качества жизни пациентов [35], об-ладают липидкорректирующим эффектом [36], уменьшают выраженность системного воспале-ния [37], позитивно влияют на показатели когни-тивного статуса [38]. В настоящее время большой интерес пред-ставляет использование физических тренировок высокой интенсивности, позволяющих дости-гать необходимого эффекта ишемического пре-кондиционирования у пациентов с ИБС.…”
Section: сердечно-сосудистой хирургии Fundamental Aspects Of Cardiovaunclassified
“…В послеоперационном периоде применение физи-ческой реабилитации уменьшает потери мышечной массы и количество послеоперационных респираторных осложнений [19,20,21]. Единичные исследования показали, что физические тренировки в послеоперационном периоде КШ снижают выраженность когнитивных нарушений [22]. Однако эффективность физических тренировок на предоперационном этапе реабилитации В других исследованиях тренирующие программы для восстановления когнитивных функций у кардиохирургических пациентов, показавшие улучшение функций внимания и рабочей памяти, качества жизни, использовались в послеоперационном периоде и не сопровождались физическими тренировками [24,25].…”
unclassified